Traces of survival : drawings of refugees in Iraq - Ai Weiwei; Chalabi, Tamara; Van Cauteren, Philippe (Brussel: Mercatorfonds, 2015)
"selected by Ai Weiwei ; edited by Tamara Chalabi and Philippe Van Cauteren"